General Overview of the History of Modern Ophthalmology in Nigeria: A Synopsis of Institutions, Events and Personalities - (:unkn) unknown (My University, 2021)
Ophthalmology in Nigeria has developed over the decades with contributions from several personalities. Many events and institutions have served to shape the emergence of good care, from the establishment of ECWA Eye hospital in 1943 as one of the premiere indigenous dedicated Eye Hospitals, to the establishment of the National Eye Centre as well as the University College Hospital Ophthalmology department, the specialty of Ophthalmology has grown to enviable heights. The hospital was accredited by the West African Postgraduate Medical College (WACS) for the training of Diploma in Ophthalmology. The formation of the Ophthalmological Society of Nigeria in 1969 and the establishment of the National Postgraduate College and The West African College of Surgeons equally stand out as landmark events in History.The Nigerian National Survey of Blindness and Visual Impairment (2005 to 2007) was the biggest ever survey in Africa, no national level estimates existed in Nigeria before the survey. This gigantic task took more than three years to complete including 30 months of rigorous fieldwork and was only possible because of the special efforts of key individuals. The MTN EYE FOUNDATION Eyeris Program (2013 - 2017) also stands out as a landmark surgical intervention scheme involving 12 states in all geopolitical zones in Nigeria. A total of 18,438 free cataract surgeries were performed, 23,528 eyeglasses and 23,226 ocular medications for ocular allergies, glaucoma and ocular infections were also given free to beneficiaries. The earliest records available dates the establishment of ECWA Eye Hospital Kano by Sudan Interior Mission on the 20th of January 1943 as one of the earliest indigenous dedicated eye hospital in Nigeria.
Keywords: African Research